Measuring private sphere environmentally significant behaviour of residents in Abu Dhabi. (2017) - Iyanna, Shilpa; Papastathopoulos, Avraam
The ecological footprint of the United Arab Emirates is one of the highest in the world. Concentrated efforts are being made by the government of UAE towards promoting and facilitating sustainable behaviour. These efforts are based on the premise that enhancing knowledge and awareness of environmental problems can lead to a change in behaviour. The aim of this paper is to: 1) examine private sphere environmentally significant behaviour focused around specific sustainable activities such as green consumption, recycling, energy saving and water conservation; 2) present and validate environmentally significant behaviour as a second-order construct capable of capturing multiple behavioural dimensions. The results will offer policy makers insight into how effective their efforts have been on everyday practices of individuals. Considering the dearth of research in this area in the UAE, this study could provide academics with future research opportunities that explore various aspects of sustainable consumer behaviour in this region.